Chitinase (CHI) of Spodoptera frugiperda affects molting development by regulating the metabolism of chitin and trehalose - Liu, Xiang-Yu; Wang, Sha-Sha; Zhong, Fan; Zhou, Min; Jiang, Xin-Yi; Cheng, Yi-Sha; Dan, Yi-Hao; Hu, Gao; Li, Can; Tang, Bin; Wu, Yan (Frontiers in Physiology, 2022)
Insect molting is the result of the balance and coordination of chitin synthesis and degradation in chitin metabolism under the action of hormones. In this study, a 678 bp dsRNA fragment was designed and synthesized according to the known CHI (Chitinase) sequence of Spodoptera frugiperda. It was injected into the larvae to observe the molting and development of S. frugiperda. At the same time, the activity of trehalase and chitinase, the content of trehalose and chitin and other substances were detected, and the expression of moderate genes in the chitin synthesis pathway was determined. The results showed that CHI gene was highly expressed at the end of each instar, pre pupa and pupal stage before molting; In the first 24 hours after dsRNA injection of CHI gene of S. frugiperda, the expression of CHI gene was significantly decreased, and the chitinase enzyme activity was significantly decreased from 12 h to 48 h. The expression of CHSB gene was significantly decreased, and the chitin content was significantly increased. Some larvae could not molt normally and complete development, leading to certain mortality. Secondly, after RNAi of CHI gene, the content of glucose and glycogen increased first and then decreased, while the content of trehalose decreased significantly or showed a downward trend. The two types of trehalose and trehalose genes decreased first and then increased, especially the trehalose enzyme activity was significantly increased 48 h after dsRNA injection of CHI gene. And TPS, GFAT, UAP, HK, G6PI and PAGM all decreased significantly at 24 h, and then increased or significantly increased at 48 h. These results indicate that when the expression of chitinase gene of S. frugiperda is inhibited, it will cause the degradation of chitin in the old epidermis and the formation of new epidermis, and the chitin content will rise, resulting in its failure to molt and develop normally. Moreover, the chitin synthesis pathway and trehalose metabolism are also regulated by reaction. The relevant results provide a theoretical basis for screening target genes and developing green insecticides to control pests by using the chitin metabolism pathway.